Mortality among the early cases of COVID-19 and its association with key comorbidities in a large state in South India - Bhat, Suhas; Kolla, Rohan; Shindhe, Shashank D.; Munoli, Surekha B. (International Journal Of Community Medicine And Public Health, 2020)
Background: The mortality associated with the pandemic COVID-19 is a subject of intense scrutiny as COVID-19 can cause severe disease leading to hospitalization in ICU and potentially death, especially in the elderly with comorbidities. A statistical analysis is carried out to study the impact of age, gender and comorbidities on deaths among early one lakh infected population of Karnataka, a large state in south India. Methods: Daily case fatality rate and adjusted case fatality rate (CFR) (adjusted to median death time) are estimated. The impacts of age, gender and comorbidities on mortality outcomes of COVID patients are studied. Results: The daily CFR on 27th July for Karnataka is estimated from the dataset to be 1.93%. However, the adjusted CFR based on the median number of days from diagnosis to death was found to be 2.15% (95% confidence interval 2%-2.3%) on that day. The deaths among male patients outnumber those in females. As far as age of the patients is concerned, more than 50% of the deaths occurred in the age group 50-60 and 60-70 years. Majority of deaths reported in the state were associated with at least one of the comorbidity. Diabetes mellitus and hypertension were the most significant comorbidities. Conclusions: The daily adjusted CFR for the study region is found to be lower than the CFR of the whole nation. Also the age, gender and comorbidities were found to be associated with the deaths as opposed to the infection alone. It was also deduced that, patients with a history of diabetes or hypertension or ischemic heart disease or a combination of any of these were most likely to experience severe outcomes of the infection.